2007
DOI: 10.1016/s0917-2394(07)70099-x
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of gum component in saliva before and after swallowing during prolonged gum chewing

Abstract: OBJECTIVES: The concentration of the substances eluted from the gum into saliva before and after swallowing has not almost carried out. The purpose of this study was to measure the volume of saliva before (VMAX) and after (RESID) swallowing in the mouth and was also to measure the concentration of the component (sugar) eluted from the gum chewing. METHODS: The RESID was measured by a dilution method (Lagerlof and Dawes, 1984). It was computed by measuring the potassium concentration in saliva and in the expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For decades, dentists discouraged the use of chewing gum due to sucrose additives. However, evidence showed that chewing gum would promote enamel remineralization by stimulating saliva flow and increasing plaque pH ( 36 , 37 ). Chewing gum can be easily found with non-sugar sweeteners such as xylitol.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, dentists discouraged the use of chewing gum due to sucrose additives. However, evidence showed that chewing gum would promote enamel remineralization by stimulating saliva flow and increasing plaque pH ( 36 , 37 ). Chewing gum can be easily found with non-sugar sweeteners such as xylitol.…”
Section: Discussionmentioning
confidence: 99%